Hak-hak Dasar Lingkungan Hidup dalam Ajaran “Saminisme” Perspektif Konstitusi Republik Indonesia - Muhammad Maghfur Agung; Yusuf Eko Nahuddin (Journal of Sharia and Legal Science, 2023)
This study aims to examine basic environmental rights in accordance with the teachings of Saminism and their arrangements in the constitution. This study uses a type of normative research. The approach used is the conceptual approach and the statutory approach. The results of the study reveal that there are five basic environmental rights according to the teachings of saminism, namely the right to be managed properly, the right to be planted, the right to be protected, the right to be preserved, and the right to be used as necessary. However, the constitution of the Republic of Indonesia has not regulated this matter. Liability to the environment is regulated in the Environmental Protection and Management law, but the form of the obligation is unclear. Therefore, obligations to the environment need to be regulated clearly and unequivocally, both in the constitution and regulations under it.